Two regimens of sultamicillin in treating uncomplicated gonorrhoea. Issue 1 (February 1985) - Farthing, C; Thin, R N; Smith, S; Phillips, I
Abstract : Sultamicillin is a covalent union of ampicillin and the beta lactamase inhibitor, sulbactam (CP-45, 899). Two studies were conducted to assess its efficacy in treating uncomplicated gonorrhoea. In the first study treatment comprised sultamicillin 1.5 g and probenecid 1 g; 124 (89.2%) of 139 patients responded including seven of 11 patients harbouring beta lactamase (penicillinase) producing strains of Neisseria gonorrhoeae (PPNG). In the second study sultamicillin 2.25 g and probenecid 1 g were given; 122 (93.8%) of 130 patients responded. Only two of seven pharyngeal infections resolved, and if pharyngeal infections are excluded the overall cure rate rose to 95.3%. Thirteen of 14 patients infected with PPNG strains were cured by the larger dose. Side effects were mild and transitory. It may be concluded that sultamicillin 2.25 g plus probenecid 1 g is an effective regimen to treat uncomplicated rectal and genital gonorrhoea and is useful for treating infections with PPNG strains. Most beta lactamase resistant antimicrobials must be given parenterally; sultamicillin is given by mouth.